2023
DOI: 10.1371/journal.pone.0284246
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility analysis of integrating community-based health insurance schemes into the national health insurance scheme in Uganda

Abstract: Background Uganda has a draft National Health Insurance Bill for the establishment of a National Health Insurance Scheme (NHIS). The proposed health insurance scheme is to pool resources, where the rich will subsidize the treatment of the poor, the healthy will subsidize the treatment of the sick, and the young will subsidize the treatment of the elderly. However, there is still a lack of evidence on how the existing community-based health insurance schemes (CBHIS) can fit within the proposed national scheme. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Kenya has higher per capita health care expenditure than Tanzania or Uganda, and while out-of-pocket costs are reducing year on year, they still make up a substantial share of spending in all three countries [ 15 ]. Health insurance coverage is far from universal [ 16 ], but is highest in Kenya, lower in Tanzania [ 17 ], and lowest in Uganda, where development of a national health insurance scheme is ongoing [ 18 ]. Finally, while drug sellers and pharmacies play a vital role in providing access to medication in all three countries [ 19 ], access to ABs without prescription through these outlets is relatively common [ 10 , 18 , 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kenya has higher per capita health care expenditure than Tanzania or Uganda, and while out-of-pocket costs are reducing year on year, they still make up a substantial share of spending in all three countries [ 15 ]. Health insurance coverage is far from universal [ 16 ], but is highest in Kenya, lower in Tanzania [ 17 ], and lowest in Uganda, where development of a national health insurance scheme is ongoing [ 18 ]. Finally, while drug sellers and pharmacies play a vital role in providing access to medication in all three countries [ 19 ], access to ABs without prescription through these outlets is relatively common [ 10 , 18 , 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Health insurance coverage is far from universal [ 16 ], but is highest in Kenya, lower in Tanzania [ 17 ], and lowest in Uganda, where development of a national health insurance scheme is ongoing [ 18 ]. Finally, while drug sellers and pharmacies play a vital role in providing access to medication in all three countries [ 19 ], access to ABs without prescription through these outlets is relatively common [ 10 , 18 , 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the MBUSO scheme has been in existence since 2006, the scheme officials indicated that enrollments were still sub-par and that there was a trust deficit from potential members. We recommend interventions aimed at promoting enrollment in community-managed health insurances schemes such as grass root demand creation campaigns, financial incentives for enrollment and the use of social media innovations to increase uptake in the informal sector as well as promoters such as civil society organizations [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Uganda, the CBHI schemes which are relatively well documented are those which are provider-based [ 15 , 16 ]. On the other hand, there is comparatively less empirical attention towards CBHI schemes initiated and managed by community members themselves in Uganda which account for 14% of all CBHI schemes in Uganda [ 17 , 18 ]. This paper begins to fill this gap.…”
Section: Introductionmentioning
confidence: 99%
“…As it has been mentioned above, the coverage of healthcare insurance is suboptimal, this means that access to quality healthcare is also limited, especially among the rural poor people. This leaves the majority with high out-of-pocket health expenditures in trying to access healthcare [8]. Those that may not afford to pay, may end up losing their lives before seeking or even receiving appropriate healthcare.…”
Section: Introductionmentioning
confidence: 99%